Răspuns :
a) x= -1 supra 2
b) 2x+3-3x=1
-x=-2
x=2
d)
[tex] {x}^{2} - 2x + 1 = 1 + {x}^{2} + 2x + 4[/tex]
-4x+1=5
-4x=4
x=-1
e) radical din 2
f) x1=0
x2=1 supra 2
x3=-2
b) 2x+3-3x=1
-x=-2
x=2
d)
[tex] {x}^{2} - 2x + 1 = 1 + {x}^{2} + 2x + 4[/tex]
-4x+1=5
-4x=4
x=-1
e) radical din 2
f) x1=0
x2=1 supra 2
x3=-2
a) 4x = - 2; x = - 2 / 4 ⇒ x = - 1/2
b) 2 x + 3 ( 1 - x ) = 1
2 x + 3 - 3 x = 1
- x = 1 - 3
- x = - 2 l : ( - )
x = 2
d)
(x-1)²=1+(x+2)²
x² - 2x + 1 = 1 + x² + 4 x + 4
x² - x² - 2 x - 4 x = 5 - 1
- 6 x = 4
x = - 4 / 6 = - 2 / 3
e)
x²-3+1=0
x² = 2
x =√2
f)
x ( 2 x - 1 ) ( x + 2 )=0
1) x = 0
2) 2 x - 1 = 0 ⇒ 2 x = 1 ⇒ x = 1/2
3) x + 2 = 0 ⇒ x = - 2
b) 2 x + 3 ( 1 - x ) = 1
2 x + 3 - 3 x = 1
- x = 1 - 3
- x = - 2 l : ( - )
x = 2
d)
(x-1)²=1+(x+2)²
x² - 2x + 1 = 1 + x² + 4 x + 4
x² - x² - 2 x - 4 x = 5 - 1
- 6 x = 4
x = - 4 / 6 = - 2 / 3
e)
x²-3+1=0
x² = 2
x =√2
f)
x ( 2 x - 1 ) ( x + 2 )=0
1) x = 0
2) 2 x - 1 = 0 ⇒ 2 x = 1 ⇒ x = 1/2
3) x + 2 = 0 ⇒ x = - 2